Do you have a question for me? How children with Williams syndrome respond to ambiguous referential communication during a joint activity*. Issue 1 (10th August 2012) - SKWERER, DANIELA PLESA; AMMERMAN, EMILY; TAGER-FLUSBERG, HELEN
ABSTRACT: Research on language in individuals with Williams syndrome (WS) has been fueled by persistent theoretical controversies for two decades. These shifted from initial focus on dissociations between language and cognition functions, to examining the paradox of socio-communicative impairments despite high sociability and relatively proficient expressive language. We investigated possible sources of communicative difficulties in WS in a collaborative referential communication game. Five- to thirteen-year-old children with WS were compared to verbal mental age- and to chronological age-matched typically developing children in their ability to consider different types of information to select a speaker's intended referent from an array of items. Significant group differences in attention deployment to object locations, and in the number and types of clarification requests, indicated the use of less efficient and less mature strategies for reference resolution in WS than expected based on mental age, despite learning effects similar to those of the comparison groups, shown as the game progressed.